Dilbert Gives You the Business - Scott Adams (Kansas City, United States Andrews McMeel Publishing, 1999)
Everyone who reads DILBERT and works in an office will appreciate this collection, "Dilbert Gives You the Business." Creator Scott Adams tells it like it is through the insane business world inhabited by Dilbert. If frustration and lunacy are an inevitable part of your workday, appropriate measures must be taken immediately. Andrews McMeel has the perfect antidote to your workplace stress. "Dilbert" is universally recognized as the definitive source of office humor. What makes this 14th "Dilbert" book so unique is that it is a collection of the most popular strips requested by fans for reprints and downloads from Dilbert.com gathered together. Arranged by topics for quick reference, this hilarious book is the comprehensive "Dilbert" source book, sure to alleviate work burnout. Packed within these colorful pages, fans will find all their favorite characters, including Dilbert, as he encounters daily issues from delegating to decision-making, trade shows to telecommuting, and downsizing to annoying coworkers. It's business as usual for the Dilbert clan. . . . Dilbert is continually updating his resume, Dogbert continues his pursuit of world domination, Wally strives to do the least amount of work possible, and Alice is eternally frustrated by the Boss. Welcome to the all-too-familiar world of Dilbert-the lowly engineer who has become an icon for oppressed and burntout workers everywhere! The most popular business-oriented cartoon in the world, "Dilbert" speaks to millions of fans who toil in the corporate trenches. No matter how outrageous a tale he spins, "Dilbert" creator Scott Adams inserts sufficient nuggets of truth in every strip to keep his believers laughing. In part, that's because "Dilbert" is based on his own former corporate experiences-and is kept current by culling inspiration from the 350-plus E-mails he receives each day. Keep "Dilbert Gives You the Business" close at hand-as you would your phone book, Internet diversion tool, browser, and any other work.
Keywords: Graphic Novel -- Graphic Novel; Comics -- Comics